Urban Pollutant Dispersion on a Turbulent Fluid Model - Silva, V. A.; Zaze, E. G.; Bastos, P. A.; Devecchi, F. P.; Kolicheski, M. B. (Trends in Computational and Applied Mathematics, 2023)
In 2019, more than 90% of the world’s population was living in places where pollutant concentrations exceeded the air-quality guidelines. Anthropogenic activity has been the main cause of climate change in the last 20 years, especially in urban centres where industrial activities and motorized traffic mainly occur. This article presents a study of air pollutant dispersion by computational fluid dynamics modelling using OpenFOAM for urban street canyon simulations. The aim of this study was to investigate the influence of vegetation on natural ventilation, dispersion and CO2 mitigation. The behavior of pollutants was modeled by the Reynolds-averaged Navier–Stokes equations (RANS) and the k−ε fluid turbulence model. The results indicate that aerodynamic effects are more important at lower pollutant wind velocities, as they reduce turbulent dispersion and allow a higher reduction in the concentration of air pollutants. In addition, the direction of the wind, relative to the main axis of the street, had a significant impact on the results found. In general, in the presence of trees, perpendicular winds can lead to higher concentration of pollutants, while parallel winds allow improve air quality, considerably reducing those pollutant concentrations.